The attitudes of neonatal professionals towards end-of-life decision-making for dying infants in Taiwan. Issue 6 (5th May 2012) - Huang, Li-Chi; Chen, Chao-Huei; Liu, Hsin-Li; Lee, Ho-Yu; Peng, Niang-Huei; Wang, Teh-Ming; Chang, Yue-Cune
Abstract : The purposes of research were to describe the neonatal clinicians' personal views and attitudes on neonatal ethical decision-making, to identify factors that might affect these attitudes and to compare the attitudes between neonatal physicians and neonatal nurses in Taiwan. Research was a cross-sectional design and a questionnaire was used to reach different research purposes. A convenient sample was used to recruit 24 physicians and 80 neonatal nurses from four neonatal intensive care units in Taiwan. Most participants agreed with suggesting a do not resuscitate (DNR) order to parents for dying neonates (86.5%). However, the majority agreed with talking to patients about DNR orders is difficult (76.9%). Most participants agree that review by the clinical ethics committee is needed before the recommendation of 'DNR' to parents (94.23%) and nurses were significantly more likely than physicians to agree to this (p=0.043). During the end-of-life care, most clinicians accepted to continue current treatment without adding others (70%) and withholding of emergency treatments (75%); however, active euthanasia, the administration of drug to end-of-life, was not considered acceptable by both physicians and nurses in this research (96%). Based on our research results, providing continuing educational training and a formal consulting service in moral courage for neonatal clinicians are needed. In Taiwan, neonatal physicians and nurses hold similar values and attitudes towards end-of-life decisions for neonates. In order to improve the clinicians' communication skills with parents about DNR options and to change clinicians' attitudes for providing enough pain-relief medicine to dying neonates, providing continuing educational training and a formal consulting service in moral courage are needed.